2023
DOI: 10.1021/acs.estlett.3c00497
|View full text |Cite
|
Sign up to set email alerts
|

Triazine-Derived Ultraviolet Filters and Flame Retardants: A Nationwide Co-Occurrence and Prevalence Study in China

Jiali Ge,
Jiehua Li,
Xu Han
et al.

Abstract: Triazine-derived ultraviolet filters (TA-UVFs) and flame retardants (TA-FRs) have been increasingly used for industrial needs. However, there remains a gap in knowledge regarding their co-occurrences and prevalence trends in municipal sludge on a large scale. Here, we conducted the first national-scale survey of wastewater-derived TA-UVFs and TA-FRs in the sludge of China. A total of 17 TA-UVFs and 6 TA-FRs were detected in the nationwide sludge samples. Among the 23 target triazine chemicals, 17 were reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The occurrence of organic contaminants in biosolids, referred to here as biosolid-associated organic contaminants (BOCs), has been studied for decades in the U.S. and internationally, , with some specific classes of chemicals receiving increased attention, including pharmaceuticals, chemicals used in personal care products, flame retardants, , ultraviolet (UV) filters, , and per- and polyfluorinated alkyl substances (PFASs). , As required by the Clean Water Act, the EPA conducts reviews every two years to identify additional contaminants in biosolids and sets limits if those contaminants are determined to pose a health risk to humans or the environment . The EPA′s Biennial Reviews and National Sewage Sludge Surveys identified chemicals present in U.S. and Canadian biosolids, and the results were recently curated, with updated versions publicly available on the EPA′s CompTox Chemicals Dashboard (hereafter “the Dashboard”).…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of organic contaminants in biosolids, referred to here as biosolid-associated organic contaminants (BOCs), has been studied for decades in the U.S. and internationally, , with some specific classes of chemicals receiving increased attention, including pharmaceuticals, chemicals used in personal care products, flame retardants, , ultraviolet (UV) filters, , and per- and polyfluorinated alkyl substances (PFASs). , As required by the Clean Water Act, the EPA conducts reviews every two years to identify additional contaminants in biosolids and sets limits if those contaminants are determined to pose a health risk to humans or the environment . The EPA′s Biennial Reviews and National Sewage Sludge Surveys identified chemicals present in U.S. and Canadian biosolids, and the results were recently curated, with updated versions publicly available on the EPA′s CompTox Chemicals Dashboard (hereafter “the Dashboard”).…”
Section: Introductionmentioning
confidence: 99%